Boom-bust cycles and financial liberalization - Tornell, Aaron; Westermann, Frank 1970- (The MIT Press, 2005)
The volatility around financial crises that have hit many middle-income countries (MICs) after they liberalize their financial markets has prompted critics to call for new policies to stabilize these boom-bust cycles. But, as Aaron Tornell and Frank Westermann point out in this book, over the last two decades most of the developing countries that have experienced lending booms and busts have also exhibited the fastest growth among MICs. Countries with more stable credit growth, by contrast, have exhibited, on average, lower growth rates. Factors that contribute to financial fragility thus appear, paradoxically, to be a source of long-run growth as well. Tornell and Westermann analyze boom-bust cycles in the developing world and discuss how these cycles are generated by credit market imperfections. They explain why the financial liberalization that allows countries to overcome imperfections impeding rapid growth also generates the financial fragility that leads to greater volatility and occasional crises. The conceptual framework they present illustrates this linkage and allows Tornell and Westermann to address normative questions regarding liberalization policies. The authors also characterize key macroeconomic regularities observed across MICs, showing that credit markets play a key role not only in boom-bust episodes but in the strong "credit channel" observed during tranquil times. A theoretical framework is then presented that explains how credit market imperfections can account for these empirical patterns. Finally, Tornell and Westermann provide microeconomic evidence on the credit market imperfections that drive the results of the theoretical framework, finding that asymmetries between tradables and nontradables are key to understanding the patterns in MIC data.
Literaturverz. S.167-174
Keywords: Business cycles; Crises financières - Pays en voie de développement; Crédit - Pays en voie de développement; Finances - Pays en voie de développement; Financiële crises; Internationale Kapitalbewegung; Konjunktur; Unvollkommener Markt; Wirtschaftswachstum; Entwicklungsländer; Credit -- Developing countries; Finance -- Developing countries; Financial crises -- Developing countries; Schwellenländer